The Study of Prevalence of Hypercholesterolemia and some Relative Factors in Golestan Province - E Tazik; A Angizeh; F Niknezhad; SM Sedaghat; SA Hoseini; H Joshaghani; GhR Veghari; P Maharloei (Tehran University of Medical Sciences, 2010)
Background and Aim: Cardiovascular disease is the first and for most factor for mortality in adults and hypercholesterolemia (HC) is a susceptible agent for them. The main objective of this study is to determine the of prevalence of HC and some risk factors related to it in adults in Golestan province in 2006.Materials and Methods: This is a Crossectional-Descriptive study based on population and 1995 cases (997 men and 998 woman) between 25- 65 years old, were chosen by cluster and stratify sampling in Golestan adult population. We interviewed all the cases and determined anthropometric and biochemical indexes. Data was analyzed by SPSS.14 software. HC was defined as serum cholesterol levels over 200 mg/dl.Results: Mean age was 39.2 year and mean ±SD of serum cholesterol in men and women was 196.7±39.11 and 209.4± 42.9 respectively. Prevalence of HC showed significant deference between men (44.7%) and women (57%) (P<0.05). There is a significant difference between age groups, region, physical activity and BMI in the mean value of serum cholesterol (P<0.01) but regarding economic status it is not significant. Prevalence of HC in abdominal obese and healthy group is 63.2% and 41% respectively and statistical difference is significant (P<0.05). The people of Golestan province consume fruits , vegetables and fish 4.84, 3.65 and 2 days in a week respectively and vegetable and fish are consumed more in HC group than in non- HC group. The consumption of hydrogenated oil, liquid oil and other type of oils is 85.4% ,14% and 0.7% respectively, and in HC people the intake of liquid oil is slightly higher than others, but statistical differences is not significant.Conclusions: HC is one of the most health problems in Golestan province and women suffer from it more then men. Life style and food behavior are two risk factors for it. Thereby correction of food and social behavior can decline incidence of cardiovascular disease.